2017
DOI: 10.1111/ijpo.12218
|View full text |Cite
|
Sign up to set email alerts
|

Parental beliefs about portion size, not children's own beliefs, predict child BMI

Abstract: SummaryBackgroundIncreases in portion size are thought by many to promote obesity in children. However, this relationship remains unclear. Here, we explore the extent to which a child's BMI is predicted both by parental beliefs about their child's ideal and maximum portion size and/or by the child's own beliefs.MethodsParent–child (5–11 years) dyads (N = 217) were recruited from a randomized controlled trial (n = 69) and an interactive science centre (n = 148). For a range of main meals, parents estimated thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…showed a positive correlation between the portion size a parent thought perfect for their child (aged 5–11 years) to eat for dinner and the portion size their child thought perfect for themselves ( r = 0.15, P < 0.05) . Equally, the maximum portion size a parent thought their child would eat for dinner correlated positively with the maximum portion size their child thought they would eat for dinner ( r = 0.22, P < 0.001) . Marx et al .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…showed a positive correlation between the portion size a parent thought perfect for their child (aged 5–11 years) to eat for dinner and the portion size their child thought perfect for themselves ( r = 0.15, P < 0.05) . Equally, the maximum portion size a parent thought their child would eat for dinner correlated positively with the maximum portion size their child thought they would eat for dinner ( r = 0.22, P < 0.001) . Marx et al .…”
Section: Resultsmentioning
confidence: 95%
“…Ages of parents' children were younger in qualitative studies (1–5 years in 9/14, 5–13 in 3/14 and 2–12 in 1/14), compared with quantitative studies (2–6 years in 5/14 studies, 5–12 in 6/14 and 3–13 in 3/14). Most quantitative studies were observational (12/14) and used questionnaires , portion size estimation or portioning tasks , a home meal portioning observation or a computer‐assisted interview . Remaining quantitative studies (2/14) were experimental in design but reported data from baseline questionnaires .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of parent as models would extend to the food environment of the home as well as their expression of conscious and unconscious beliefs and expectations about food and diet (the modeling scales developed by Palfreyman et al [ 150 ] show ways in which parents could provide models). The food environment includes the availability of energy-dense foods, the types and availability of snack foods, and portion sizes e.g., [ 151 , 152 ]. Parent and child disinhibited eating clearly is related to the family and wider social and psychological context.…”
Section: Biology Integrated With Psychosocial Processesmentioning
confidence: 99%
“…Studies on self regulation of the food by children have demonstrated that parenting practices of providing food based on environmental cues like time of dinner rather than the hunger itself affect child's self regulation ability. 38,39 As early as 3-5 years of age, children have shown little evidence of ability to adjust food intake in response to the altered energy density of food thus leading to increased amounts of intake. 40 Control of feeding practice has been credited to the findings that suggest that fathers may play a role in the control of feeding practices since daughters whose fathers were stricter on control of food had a higher percent of fat.…”
mentioning
confidence: 99%